Cannabis exposure and risk of testicular cancer: a systematic review and meta-analysis. Issue 1 (December 2015) - Gurney, J.; Shaw, C.; Stanley, J.; Signal, V.; Sarfati, D.
Abstract Background The aetiology of testicular cancer remains elusive. In this manuscript, we review the evidence regarding the association between cannabis use and testicular cancer development. Methods In this systematic review and meta-analysis, we reviewed literature published between 1st January 1980 and 13th May 2015 and found three case–control studies that investigated the association between cannabis use and development of testicular germ cell tumours (TGCTs). Results/Conclusions Using meta-analysis techniques, we observed that a) current, b) chronic, and c) frequent cannabis use is associated with the development of TGCT, when compared to never-use of the drug. The strongest association was found for non-seminoma development – for example, those using cannabis on at least a weekly basis had two and a half times greater odds of developing a non-seminoma TGCT compared those who never used cannabis (OR: 2.59, 95 % CI 1.60–4.19). We found inconclusive evidence regarding the relationship between cannabis use and the development of seminoma tumours. It must be noted that these observations were derived from three studies all conducted in the United States; and the majority of data collection occurred during the 1990's.